Multi-marker phylogeny of three evergreen oaks reveals vicariant patterns in the Western Mediterranean (Taxon, 2007)
Nuclear (AFLPs and ITSs) and chloroplast DNA markers (cpDNA) were analysed in Quercus suber L., Q. ilex L. and Q. coccifera L. in order to detect vicariant patterns in the Western Mediterranean Basin populations. Clustering methods, i.e., parsimony, minimum spanning network, UPGMA and PCO, were used to obtain robust phylogenies. The Mantel test was used to check the geographic structure of the populations. Nuclear markers’ based phylogenies showed high bootstrap values at basal nodes of clusters indicative of species. Within species, Q. suber and Q. ilex showed three and two groups respectively with strong geographic structure for cytoplasmic and nuclear markers. In contrast, Q. coccifera had overlapping cpDNA lineages and nuclear markers did not show any group with strong geographic structure. Taxonomic assignation of the species was well-supported by our data. Ongoing allopatric speciation was inferred for Q. suber and Q. ilex derived from Pliocene vicariant events. Quercus coccifera showed a more homogeneous genetic pattern in the Western Mediterranean.